Electrotrawling: a promising alternative fishing technique warranting further exploration. Issue 1 (5th July 2013) - Soetaert, Maarten; Decostere, Annemie; Polet, Hans; Verschueren, Bart; Chiers, Koen
Abstract: In trawl fisheries, beam trawls with tickler chains, chain mats or bobbin ropes are used to target flatfish or shrimp. High fuel consumption, seabed disturbance and high discard rates are well‐known disadvantages of this fishing technique. These shortcomings are increasingly gaining international public and political attention, especially with the upcoming discard ban in Europe. The most promising alternative fishing technique meeting both the fisherman's aspirations, and the need for ecological progress is pulse fishing with electrotrawls. Here, the mechanical stimulation by tickler chains or bobbins is replaced by electrical stimulation resulting in reduced bottom contact, fuel costs and discards. Although a significant amount of research has been done on electrotrawls and their impact on marine organisms, most data were published in very diverse sources ranging from local non‐peer‐reviewed reports with a limited distribution to highly consulted international peer‐reviewed journals. Therefore, there is a clear need for a comprehensive yet concise and critical overview, covering and summarizing all these data and making these available for the scientific community. This article aims to meet the above goals by discussing the working principle of electric fields, the history of electrotrawls and their current application in the North Sea and impact on marine organisms. It is concluded by elaborating on the opportunities and challenges for the further implementation of this alternative fishing technique.